Occurrence and Transmission of Grapevine Virus A in South African grapevines - Engelbrecht, D .J.; Kasdorf, G. G .F. (South African Journal of Enology and Viticulture, 2017)
Antiserum prepared to a local isolate of grapevine virus A (GVA) was used in immunosorbent electron microscopy (ISEM) with decoration and in an unlabelled antibody enzyme-linked immunosorbent assay (ELISA) for the screening of grapevine sources for the presence of virus. GV A occurred extensively in grapevine plantings showing visual symp· toms of leafroll or indexing positive for leafroll. GV A was found not to be associated with either stem pitting or fleck symptoms. It occurred mostly in association with undecorated closterovirus (CV)-like particles. Limited ISEM with decoration of the CV-like particles using antiserum to a Swiss isolate of CV 2 200 nm, (CV type I) confirmed the presence of a second CV in local grapevine sources. In addition, it indicated the presence of a third CV -like particle longer than GVA. GVA together with undecorated CV-like particles were also detected in initially GVA-free LN-33 grapevines growing under field conditions and naturally infected with Ieafroll. GV A and CV type I were also present in the vine mealybug Planococcus ficus, following exposure to a grapevine source carrying these viruses. H’lwever, due to lack of CV type I antiserum, only GV A was confirmed in grapevine following controlled transmissions with P. ficus although undecorated CV -like particles were present. The reliability of the ELISA detection procedure appears to be influenced by seasonal fluctuations in GV A concentrations.